Denitrification Performance in Packed-Bed Reactors Using Novel Carbon-Sulfur-Based Composite Filters for Treatment of Synthetic Wastewater and Anaerobic Ammonia Oxidation Effluent - Wang, Yao; Liang, Baorui; Kang, Fei; Wang, Youzhao; Yuan, Zhihong; Lyu, Zhenning; Zhu, Tong; Zhang, Zhijun (Frontiers in Microbiology, 2022)
To avoid nitrate pollution in water bodies, two low-cost and abundant natural organic carbon sources were added to make up the solid-phase denitrification filters. This study compared four novel solid-phase carbon-sulfur-based composite filters, and their denitrification abilities were investigated in laboratory-scale bioreactors. The filter F4 (mixture of elemental sulfur powder, shell powder, and peanut hull powder with a mass ratio of 6:2.5:1.5) achieved the highest denitrification ability, with an optimal nitrate removal rate (NRR) of 723 ± 14.2 mg NO3–-N⋅L–1⋅d–1 when the hydraulic retention time (HRT) was 1 h. The HRT considerably impacted effluent quality after coupling of anaerobic ammonium oxidation (ANAMMOX) and solid-phase-based mixotrophic denitrification process (SMDP). The concentration of suspended solids (SS) of the ANAMMOX effluent may affect the performance of the coupled system. Autotrophs and heterotrophs were abundant and co-existed in all reactors; over time, the abundance of heterotrophs decreased while that of autotrophs increased. Overall, the SMDP process showed good denitrification performance and reduced the sulfate productivity in effluent compared to the sulfur-based autotrophic denitrification (SAD) process.